“Você tem que ficar manobrando as coisas”: lesbianidades, violências cotidianas e possibilidades de resistência - Silva, Tanieli de Moraes Guimarães (2015)
This work aims to reflect about lesbian existences daily violence and “handlings”, from life trajectories of women who have affective-sexual relationships with other women in Goiânia. The main theoretical axis consists of theorizations from Butler (2000; 2010) about gender and sexuality, Das (1999) about violence, and Ortner (2007) about agency. The method used is the Life History and the ethnographic, with participant observations carried out in bars, nightclubs, houses, among other spaces, and semi-structured interviews with ten women from 24 to 30 years old. Through the life stories presented, it is possible to see that lesbian women are marked, in a more or less intense and direct way, by daily violence, which can be embedded in all of their contexts. Two of them are problematized here: the family and the religious ones. Faced at this reality, lesbian women have to “handle things”, in other words, they have to develop strategies and abilities to defend themselves. Therefore, “handling” is a form of agency, a resistance to a heteronormative society that insists on forcing a coherence among sex, gender, desire and sexual practice. However, there is a relation of desire-violence-guilt that permeates most of the trajectories presented here, which makes it evident that resisting is not an easy task.